Evaluation of the Influence of Transitional Slot Reynolds Numbers on Ventilation Efficiency in Mechanically Ventilated Enclosures. (2015) - Cao, Shijie; Zhu, Donghao; Fan, Xueliang
Abstract: We investigate the influence of a set of transitional inlet slot Reynolds numbers (ranging from 790 to 4000) on ventilation efficiency for an indoor ventilated enclosure. These slot Reynolds numbers are directly related with supplied ventilation rates, corresponding to Air Change per Hour (ACH) 4 to 20. The low-Re-number k–ɛ model is applied for RANS simulation in the current study. The maximal local volume-averaged concentration and recirculation rate are employed to represent ventilation efficiency. We found that when increasing inlet velocities, i.e., increasing slot Reynolds numbers, the impact on turbulence levels and pollutant concentration distributions is considerable. The larger the inlet slot Reynolds number is, the smaller the pollutant concentration magnitude will become. The results also indicated that pollutant concentration ceases to decrease with the increase of slot Reynolds numbers. Moreover, it will be less dependent on the larger range of slot Reynolds numbers (for the current study, i.e. Res≥3000) and will finally tend to show an asymptotic behavior. These findings will play an important role for the design of energy-efficient ventilation systems.